FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DISMENOREA PADA MAHASISWI PRODI D III KEBIDANAN FAKULTAS ILMU KESEHATAN UNIVERSITAS RESPATI YOGYAKARTA TAHUN 2015 - Listia Dwi Febriati (Medika Respati : Jurnal Ilmiah Kesehatan, 2016)
Background: dysmenorrhoea is the most common occurrence in the first three years after menarch, although the incident may occur at the end of a woman's reproductive life. The incidence of menstrual pain in the world is very large. An average of more than 50% of women in every country experiencing menstrual pain.Purpose: To study and Explaining factors related to the student dysmenorrhoea in Yogyakarta Respati University Health Sciences Faculty at Diploma III Midwifery Program.Methods: This study used quantitative approach with cross sectional study design. This research was conducted in UNRIYO Campus 2 Faculty of Health Sciences Diploma III Midwifery Program in Jalan Tajem No. 1.5 Maguwoharjo, Sleman, Yogyakarta. Data is collected on May 16 to 19, 2015. The population of 148, the total sample sampling technique.Outcome: The study showed the incidence of dysmenorrhea as many as 102 (68.9%), knowledge of variables p = 0.005 OR = 7289 (95% CI 2664-19944), the attitude p = 0.005 OR = 7,515 (95% CI 3458-16334), menarche p = 0.013 OR = 2,605 (95% CI 1276-5319), family history of p = 0.006 OR = 3,214 (95% CI 1461-7072), anxiety p = 0538 OR = 0744, sport p = 0.007 2842 OR (95% CI 1.388- 5821), nutritional status p = 0454 OR = 1.542, smoking p = 0.005, OR = 7,959 (95% CI 3249-19498). Multivariate analysis obtained dominant variable is the attitude p = 0.005 OR = 6623.Conclusion: There is a relationship between knowledge, attitudes, menarche, family history, exercise, and smoking with the incidence of dysmenorrhoea. There is no relationship between anxiety and nutritional status and the incidence of dysmenorrhoea. Factors that influence the incidence of dysmenorrhea is variable attitude. Suggestion: in order Diploma III Midwifery Program in UNRIYO able to maintain and further improve the quality level of knowledge, the ability to think, especially on reproductive health materials. Keywords: Dysmenorrhoea, Diploma III Midwifery Program of UNRIYO, student, attitude towards dysmenorrhoea.